(untitled) (World Bulletin of Management and Law, 2023)
The article substantiates the relevance of establishing public control in the processes of liberalization, democratization of state and public administration, the judiciary, and the social sphere in Uzbekistan. The role of nongovernmental non-profit organizations, the scope of their activities, and opportunities are analyzed. The importance of NGO’s in raising the political and legal culture, social activity of citizens has been studied.